2017
DOI: 10.1111/jsbm.12315
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Based Competitive Advantages of Young Entrepreneurial Firms: Conceptual Development and Empirical Exploration

Abstract: We explore the factors that contribute to the technological distinctiveness of young entrepreneurial firms. We claim that a young firm's technological distinctiveness is partly the result of entrepreneurs and their orientations toward uncertainty. In certain locations, however, young firms have more means to invest in their technology base. We integrate these two perspectives together, and provide an original explanation and understanding of the technological distinctiveness of young entrepreneurial firms. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 88 publications
(164 reference statements)
0
16
0
Order By: Relevance
“…The variance inflation factor of constructs with two or more influencing factors (here: Attitude, VIF=1.64) is lower than the required level of five and stays even below 3.333, which shows that there is no multicollinearity [13]. The value of R 2 represents the coefficient of determination which indicates a substantial (moderate, weak) influence if the value exceeds 0.67 (0.33; 0.19) [50]. The t-values given in Table 4 and their path coefficients allow conclusions as to the validity of the formulated hypotheses.…”
Section: Structural Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…The variance inflation factor of constructs with two or more influencing factors (here: Attitude, VIF=1.64) is lower than the required level of five and stays even below 3.333, which shows that there is no multicollinearity [13]. The value of R 2 represents the coefficient of determination which indicates a substantial (moderate, weak) influence if the value exceeds 0.67 (0.33; 0.19) [50]. The t-values given in Table 4 and their path coefficients allow conclusions as to the validity of the formulated hypotheses.…”
Section: Structural Modelmentioning
confidence: 96%
“…Regarding the external environment, our findings show that all examined factors also have an impact on the attitudes towards digitalization, as all hypotheses (H3, H4, H5) could be confirmed. Surprisingly, LOOROs perception of the pressures from the near environment (Customers and Competitors) and far environment (Society) is contradicting the currently very active digital developments of the customers and the competitors [50], [53]. For the "Perceived Competitive Pressure" our results show that the perception of the "own development" compared to the digital development of the competitors is on a medium to low level, as 40% consider their own digitalization behind competitors (PC1) and 38% perceive a need to catch up (PC2).…”
Section: Structural Modelmentioning
confidence: 99%
“…Most entrepreneurs started their ventures from the bottom where they worked with firms for several years whereby they usually used to be supervisors or managers (Selvarani & Venusamy, 2015;Tornikoski et al, 2017). They might be IT illiterate and usually have much resistance to working process's changes.…”
Section: Organizational Factormentioning
confidence: 99%
“…Scholars advocate that the effect of organizational structures on firm performance is context‐specific specific (e.g., Prajogo and McDermott ; Su et al ; Tornikoski et al ). For instance, Su et al () found a positive relationship between entrepreneurial orientation and firm performance in established firms, but an inverse U‐shape in emergent ones.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…First, we contribute to the literature on small and new businesses by being one of the first studies to demonstrate that formalization occurs in the early years (see Kotey and Slade , for an exception) contrary to the life cycle deterministic assumptions about formalization happening only in later years (McKelvie and Wiklund ). Second, we add to the literature that stresses that the performance implications of organizational structures and processes are context‐specific (e.g., Prajogo and McDermott ; Su, Xie, and Li , Tornikoski, Rannikko, and Heimonen ), by providing evidence that formalization effects are contingent upon the firms' characteristics. Moreover, we build on Delmar, Davidsson, and Gartner's () call for an increased differentiation among high‐growth firms, as they do not grow in similar ways, and stress the fact that new ventures are likely to achieve high‐performance through mechanisms other than formalization.…”
Section: Introductionmentioning
confidence: 99%